The association between genetic variants at 3’-UTR and 5’-URR of HLA-G gene and the clinical outcomes of patients with leukemia receiving hematopoietic stem cell transplantation - Chen, Ding-Ping; Wang, Po-Nan; Hour, Ai-Ling; Lin, Wei-Tzu; Hsu, Fang-Ping; Wang, Wei-Ting; Tseng, Ching-Ping (Frontiers in Immunology, 2023)
Abstract In addition to the classical human leukocyte antigen (HLA) genes, the outcomes of post-hematopoietic stem cell transplantation (HSCT) are also associated with human leukocyte antigen (HLA)-related genes and non-HLA genes involved in immune regulation. HLA-G gene plays an important role in immune tolerance, assisting immune escape of tumor cells, and decrease of transplant rejection. In this study, we explored the association of genetic variants at the 3’-untranslated region (3’-UTR) and 5’-upstream regulatory region (5’-URR) of HLA-G gene with the adverse outcomes of patients with leukemia receiving HSCT. The genomic DNAs of 164 patients who had acute leukemia and received HSCT were collected for analysis. Nine single nucleotide polymorphisms (SNPs) and six haplotypes in the 3’-UTR and 27 SNPs and 6 haplotypes in the 5’-URR were selected to investigate their relationship with the development of adverse outcomes for patients receiving HSCT, including mortality, relapse, and graft-versus-host disease. Our results revealed that two SNPs (rs371194629 and rs9380142) and one haplotype (UTR-3) located in the 3’-UTR and two SNPs (rs3823321 and rs1736934) and one haplotype (G0104a) located in the 5’-URR of HLA-G were associated with the occurrence of chronic GVHD or development of any forms of GVHD. No SNP was found to associate with the occurrence of mortality and relapse for patients receiving HSCT. These SNPs and haplotypes may play important roles in regulating immune tolerance of allografts post-HSCT that can be used to predict the risk of poor outcomes after receiving HSCT and giving preventive treatment to patients on time.